On the Effect of Heparin at Various Concentrations with Particular Reference to Increased Heparin Resistance Measured by the Plasma Heparin Thrombin Time - Holger-Madsen, T (Thrombosis and Haemostasis, 1961)
The heparin thrombin time was investigated in platelet-poor citrated plasma by determining the clotting time with thrombin after addition of heparin. At increasing heparin concentrations the heparin thrombin time was prolonged, reaching a maximum at a certain concentration. At higher concentrations the effect of heparin decreased, the heparin thrombin time getting shorter. At the highest concentrations there was again a full heparin effect, the heparin thrombin time being again prolonged to a maximum. In a study of plasma from patients with increased heparin resistance, in the form of a shortening of the heparin thrombin time in relation to normal, this was found to apply within all the studied ranges of heparin concentration.